1982
DOI: 10.1126/science.7089576
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Shift Work Schedules That Disrupt Sleep Are Improved by Applying Circadian Principles

Abstract: Workers on rotating shifts dislike those aspects of their work schedules that violate circadian sleep-wake cycle physiology. Work schedule satisfaction, subjective health estimates, personnel turnover, and worker productivity improve when schedules are introduced that are designed to incorporate circadian principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1
3

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(112 citation statements)
references
References 19 publications
4
104
1
3
Order By: Relevance
“…As early as 1982, Czeisler et al (21) reported that, by changing from backward to forward rotation, the health index score of the workers increased favorably. Compared with forward rotation shift systems, backward rotation systems have further been associated with poorer physical and psychological health, including chronic fatigue (16), more unfavorable cardiac autonomic control (25), adverse changes in self-rated health, duration and quality of sleep, and unhealthy systolic blood pressure, serum glucose, uric acid and triglyceride levels (26).…”
Section: Derection Of Shift Rotation Health and Work-family Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 1982, Czeisler et al (21) reported that, by changing from backward to forward rotation, the health index score of the workers increased favorably. Compared with forward rotation shift systems, backward rotation systems have further been associated with poorer physical and psychological health, including chronic fatigue (16), more unfavorable cardiac autonomic control (25), adverse changes in self-rated health, duration and quality of sleep, and unhealthy systolic blood pressure, serum glucose, uric acid and triglyceride levels (26).…”
Section: Derection Of Shift Rotation Health and Work-family Conflictmentioning
confidence: 99%
“…To decrease the potential adverse health effects of shiftwork, the application of healthier shift systems has been suggested (16,(21)(22)(23). One of the possibilities within three-, four-, five-, or six-shift work is the choice for forward or backward rotation of shift schedules.…”
mentioning
confidence: 99%
“…This process of "quick changeovers" tends to increase absenteeism on shift-change days (Harrington, 1978). A study by Czeisler, et al (1982) found that industrial plant workers on rotating shift schedules who had a longer rotation period (21 days) compared to those who had a shorter rotation period (weekly rotation) showed increases in job satisfaction, productivity and improvements in health.…”
Section: Work Schedulesmentioning
confidence: 99%
“…Adaptation to phase-delayed schedules is easier than with phase-advanced schedules for the same reason that east-to-west transmeridian flight causes fewer jet lag symptoms than does west-to-east transmeridian flight (Melton, 1986). Czeisler (1982) therefore recommends a clockwise rotation (morning-afternoon-night) or phase-delayed rotation for rotating shift workers. The human free-running period of the sleep-wake cycle averages 25 hours; consequently, only a small phase advance with respect to the environment is allowed, but a two-to three-hour phase delay is required.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Other studies (Hawkins, 1987) also were conducted to try to find solutions to the problem of circadian dysrhythmia, and in 1982 the results of one study described a type of shift work rotation pattern designed to account for circadian rhythms and reduce the onset of internal disassociation (Czeisler, 1982). In recent years, however, agreements between the Federal Aviation Administration (FAA) management and controller unions have allowed controllers the option of working an alternate work schedule (AWS) consisting of various combinations of rotations and daily work hours.…”
Section: Statement Of Problemmentioning
confidence: 99%